Second European quality of life survey overview - Anderson, Robert; Mikulic, Branislav; Vermeylen, Greet; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
The European Quality of Life Survey (EQLS) has developed as a tool to inform the social policy debate in Europe. There is clearly a need to establish the main social challenges facing Europeans in Member States and to better understand the situation of different socioeconomic groups. However, it is also evident that data on living conditions should be complemented by information from another perspective, 'where people's feelings are treated as paramount' (Layard, 2005). This viewpoint is critical to assessing the European social model, which emphasises values of trust and tolerance, solidarity and justice.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Electronic books